2010
DOI: 10.1109/lpt.2010.2040983
|View full text |Cite
|
Sign up to set email alerts
|

Single-Sideband Modulation Based on an Injection-Locked DFB Laser in Radio-Over-Fiber Systems

Abstract: A LTE vector signal generator (OFDM 64-QAM) is generated and transmitted via RoF link. The input RF power is 0 dBm and the modulated current of DML is set to 60 mA. The EVM is tested as shown in Figure 8. As seen from the diagram, EVM is about 2% when input RF Frequency at 2 GHz with 20 M bandwidth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Transporting the W-Band MIMO signals over a single fiber will encounter severe power degradation because of fiber chromatic dispersion; therefore, the optical single side band (OSSB)+Carrier modulation technique [20] is implemented using the Mach-Zehnder modulators (MZMs) to modulate the MIMO signals (X 1 , X 2 , and X 3 ) on the three assigned carriers f 3 -f 5 , respectively, as illustrated in Fig. 4(c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transporting the W-Band MIMO signals over a single fiber will encounter severe power degradation because of fiber chromatic dispersion; therefore, the optical single side band (OSSB)+Carrier modulation technique [20] is implemented using the Mach-Zehnder modulators (MZMs) to modulate the MIMO signals (X 1 , X 2 , and X 3 ) on the three assigned carriers f 3 -f 5 , respectively, as illustrated in Fig. 4(c).…”
Section: Resultsmentioning
confidence: 99%
“…To overcome RF power degradation because of fiber dispersion, the optical single sideband with a carrier (OSSB + C) modulation technique is implemented [20]. The bit error rate (BER) calculation of overall system performance is discussed last.…”
Section: B All-optical Ofdmmentioning
confidence: 99%
“…Recently, we have demonstrated that data upconversion with single mode modulation is more promising compared with dual mode modulation for overcoming the CSE [8]. Therefore, single mode and SSB modulation is an effective way to eliminate the CSE in RoF systems [9].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon will degrade systems' performance. In order to overcome RF power degradation due to fiber dispersion, optical single sideband (OSSB) modulation technique must be implemented [2]. The fact that OSSB modulation can remove a half of the optical spectrum is expected to attain a dispersion benefit because the optical spectrum has been reduced by a factor of two.…”
Section: Introductionmentioning
confidence: 99%